Avaliação do método do balanço da camada limite para a estimativa de fluxos turbulentos noturnos - De Conti, Tatiana (2006)
This work is about to verify the performance of the boundary layer budgeting method as alternative for measuring the surface turbulent fluxes in conditions that allow the validation of the measurements with data taken from a tower equipped with sensors, which were processed through the eddy correlation method. A research is made on the knowledge generated to the present, which reveals the limitations of the eddy correlation method and the promises of the boundary layer budgeting in relation to measuring the surface turbulent fluxes. This work describes its theoretical underpinnings, regarding the energy budget in the atmosphere and the role of turbulence in the transport phenomena and in energy exchanges. These concepts are interpreted physically and described in the form of ruling equations and hypotheses used for the analysis of the behavior of such phenomena. The eddy correlation is described as a method that directly measures the sensible heat and latent heat fluxes in function of the data picked up by the sensors. The boundary layer budgeting method, by its turn, is described from the general formulation of scalar accumulation, on which are taken the hypotheses of elimination of the horizontal advection and of any sources or drains in the atmosphere. The context of the measuring work is described in the following, from the presentation of the project, its places, and its campaigns and to the day and times in which the measurements took place. The instruments used for data acquisition are also described, as well as the processing systematics of the raw data. The obtained results reveal significant differences in the sensible heat flux estimates, which increase with the progress of the night and smaller differences in the latent heat flux, which remain constant in the time.